Antioxidant Activity of Hydroalcoholic Extract of Puguntano Herbs and Andaliman Fruits by Cuprac Methods - Satria, Denny; Dalimunthe, Aminah; Sitorus, Panal; Waruwu, Syukur Berkat; Vadhila, Mumtaz; Wahyu, Muhammad (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Free radical damage to the body can be prevented and repaired using antioxidants. Various natural ingredients native to Indonesia contain antioxidants, which are needed to improve people's health at an affordable cost. Puguntano (Picria fel-terrae) and Andaliman (Zanthoxylum acanthopodium DC.) are natural ingredients that can be used as antioxidants. This research determined the antioxidant activity and differences in IC50 values of hydroalcoholic extracts from Puguntano (Picria fel-terrae Lour) herbs and Andaliman (Zanthoxylum acanthopodium Fruits). Hydroalcoholic extracts were prepared by maceration using 90%, 80%, 70%, 60% and 50% ethanol. Antioxidant capacity was measured using the CUPRAC method, and quercetin was used as a positive control. The results were showed that the IC50 value for hydroalcoholic extracts of Puguntano herbs (27.02 ± 0.15 µg/mL, 25.94 ± 0.22 µg/mL, 25.12 ±0.15 µg/mL, 22.07 ± 0.23 µg/mL, and 23.86 ±0.18 µg/mL) and for Andaliman fruits (41.65 ± 0.30 µg/mL, 36.59 ± 0.40 µg/mL, 34.13 ± 0.44 µg/mL, 25.46 ± 0.30 µg/mL, 25.39 ± 0.30 µg/mL) respectively and quercetin 2.21 ± 0.02 µg/mL. Hydroalcoholic extracts of Puguntano herbs and Andaliman fruits have antioxidant activity, with each concentration having an IC50 of less than 50 µg/mL. The test sample's antioxidant activity is indicated by its lower IC50 value.